Case Report: Mast cell anergy: absence of symptoms after accidental re-exposure to amoxicillin/clavulanic acid 3 days after anaphylaxis - Guyénard, Loris; Tauber, Marie; Debord-Peguet, Sophie; Berard, Frédéric; Nosbaum, Audrey; Hacard, Florence; Castells, Mariana; Nicolas, Jean-François (Frontiers in Allergy, 2024)
Empty mast cell syndrome, also named post anaphylaxis mast cell anergy (PAMA), is a temporary state of loss of mast cell responsiveness after a severe immediate hypersensitivity reaction. In this study, we describe a case of PAMA after accidental re-exposure to amoxicillin in a patient who developed severe anaphylaxis to this drug three days earlier in the operating room. To our knowledge, this report is the second to document this phenomenon.